Immune modulation effects of curcumin in pristane-induced lupus mice - Handono Kalim; Kusworini Handono; Takhta Khalasha; Mirza Zaka Pratama; Tri Wahyudi Iman Dantara; Ayu Pramitha Wulandari; Fahimma Albinsaid; Sofi Nur Fitria; Muhammad Vardian Mahardika (Indian Journal of Rheumatology)
Background: Curcumin, a polyphenolic compound derived from food spice turmeric has been widely used in Asian traditional medicine for its medicinal properties as antitumor, antioxidant, and anti-inflammatory properties. Meanwhile, intraperitoneal (i.p.) injection of the hydrocarbon oil pristane into normal mice leads to a lupus-like autoimmune syndrome. We aimed to investigate the effects of curcumin on systemic lupus erythematosus (SLE) clinical manifestation, adaptive immune system components, proinflammatory cytokines, and autoantibody production in pristane-induced lupus mice. Methods: Fifty female BALB/c mice, 6–8 weeks old were divided into 2 groups: Forty mice received a single i.p. injection of 0.5 cc pristane for lupus induction and ten mice as healthy controls. Starting at 16 weeks after injection, forty pristane-induced lupus mice were divided into four groups based on doses of curcumin received intragastrically: 0, 12.5, 50, and 200 mg/kg bw/day daily for 16 weeks. At 32 weeks after injection, all of mice were assessed for arthritis score, proteinuria level, body weights, adaptive immune system components (Th1, Th2, Th17, and Treg percentages) from spleen using flow cytometry; proinflammatory cytokines and autoantibody production, including interleukin-6 (IL-6), interferon-alpha (IFN-α), and antinuclear antibody (ANA) from serum using enzyme-linked immunosorbent assay. Results: Arthritis score and proteinuria level were decreased in curcumin-treated mice. However, body weights were not significantly different between the groups. The decreased of Th1, Th2, and Th17 percentages were seen after treatment with 200 mg/kg bw/day of curcumin (P = 0.031,P = 0.017, andP = 0.005, respectively). However, only slight increase of Treg percentages was seen after curcumin treatment. Treatment with 200 mg/kg bw/day of curcumin decreased serum IL-6 and IFN-α levels (P = 0.007 andP = 0.003). Furthermore, ANA levels were also decreased significantly after treatment with 200 mg/kg bw/day of curcumin (P = 0.013). Conclusion: Our findings suggested that curcumin could prove useful as a therapeutic intervention in SLE.